2016
DOI: 10.1111/ppa.12526
|View full text |Cite
|
Sign up to set email alerts
|

Measuring lesion attributes and analysing their spatial patterns at the leaf scale using digital image analysis

Abstract: Digital image analysis was used to quantify size, shape and relative positions of individual plant disease lesions to determine their spatial distribution pattern at the leaf scale. Rice brown spot was used as a necrotrophic pathogen causing numerous discrete lesions. A 50‐leaf subsample was selected from an existing data set of 350 images of leaves taken from the field, and analysed for disease severity using image analysis. Further measurements included size, shape and the relative positions of lesions for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…However, obtaining FL images, which required harvesting leaf samples, positioning them, and capturing the image, took 140 s per plant. Schwanck and Del Ponte (2016) noted that leaf sampling and lesion counting is labor intensive and that visual estimates of severity may be faster. This was certainly the case in our study; however, gains in precision and accuracy for diseases such as stem rust at the cost of up‐front time expenses might be worthwhile for many researchers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, obtaining FL images, which required harvesting leaf samples, positioning them, and capturing the image, took 140 s per plant. Schwanck and Del Ponte (2016) noted that leaf sampling and lesion counting is labor intensive and that visual estimates of severity may be faster. This was certainly the case in our study; however, gains in precision and accuracy for diseases such as stem rust at the cost of up‐front time expenses might be worthwhile for many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three had no experience rating rust but had routinely applied visual scales to plants in the field. A review of the literature shows that rater panels vary greatly in size, from three to 12 (Karcher and Richardson, 2003; Godoy et al, 2006; Schwanck and Del Ponte, 2016; Nuñez et al, 2017; Pedroso et al, 2011), thus we determined that nine would give an adequate representation of what could be commonly found within the plant sciences for rating rusts on a visual scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, 67 comparing the molecular and quantitative genetic basis of resistance using lesion size versus 68 the underlying biochemical plant resistance responses has shown that different genes can 69 contribute to these traits. This suggests that the lesion size measurements are not providing the 70 full picture of the resistance response (Rowe and Kliebenstein, 2008;Bock et al, 2010;Li et al, 71 2015;Corwin et al, 2016b;Schwanck and Del Ponte, 2016;Barbedo, 2017;Matsunaga et al, 72 2017). There has been recent interest in extending our understanding of plant-pathogen 73 resistance by conducting more extensive phenotyping of disease symptoms, including 74 hyperspectral imaging of lesions that records spectra from the visible into the infrared range 75 (Montes et al, 2007;Kuska et al, 2015;Mutka and Bart, 2015;Leucker et al, 2016).…”
Section: Introduction 37mentioning
confidence: 99%